Perancangan Smart Stick untuk Mobilitas Penyandang Tunanetra Berbasis Mikrokontroler - Estu Prayoga; Arif Setia Sandi A; Khoirun Nisa (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The development of assistive technology for visually impaired individuals is essential to enhance their mobility and safety. This research successfully designed and developed a Smart Stick based on a microcontroller, equipped with ultrasonic and water level sensors to detect obstacles and water puddles in real-time. The system provides immediate warnings through a speaker, allowing users to navigate their environment more effectively. The testing phase demonstrated that the ultrasonic sensor accurately detects obstacles within a range of 50–150 cm, while the water level sensor activates an alarm when the water reaches 40 mm. The results indicate that the Smart Stick is reliable in detecting obstacles and providing early warnings, improving the independence and security of visually impaired users. Future improvements may include IoT integration, Bluetooth headset compatibility, and enhanced sensor accuracy to optimize its functionality.